2016
DOI: 10.3390/s16060805
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Interacting Multiple Model Filtering Algorithm Based on the Cubature Kalman Filter for Maneuvering Target Tracking

Abstract: In order to improve the tracking accuracy, model estimation accuracy and quick response of multiple model maneuvering target tracking, the interacting multiple models five degree cubature Kalman filter (IMM5CKF) is proposed in this paper. In the proposed algorithm, the interacting multiple models (IMM) algorithm processes all the models through a Markov Chain to simultaneously enhance the model tracking accuracy of target tracking. Then a five degree cubature Kalman filter (5CKF) evaluates the surface integral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 23 publications
0
42
0
Order By: Relevance
“…Therefore, we choose 5thSSRCKF as the filtering algorithm in the IMM framework, and propose interacting multiple model fifth-degree spherical simplex-radial cubature filter (IMM5thSSRCKF) algorithm for maneuvering target tracking of nonlinear system. Simulation results show that the IMM5thSSRCKF exhibits better performance than IMMUKF, IMMCKF and IMM5thCKF [26] in terms of accuracy and switching response.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, we choose 5thSSRCKF as the filtering algorithm in the IMM framework, and propose interacting multiple model fifth-degree spherical simplex-radial cubature filter (IMM5thSSRCKF) algorithm for maneuvering target tracking of nonlinear system. Simulation results show that the IMM5thSSRCKF exhibits better performance than IMMUKF, IMMCKF and IMM5thCKF [26] in terms of accuracy and switching response.…”
Section: Introductionmentioning
confidence: 97%
“…Although the IMMCKF algorithm and the IMM5CKF algorithm have already achieved good results [14,18], they still cannot effectively solve the problem of low filtering precision and slow convergence in the tracking process, therefore, an interactive multimodel adaptive five-degree cubature Kalman algorithm based on fuzzy logic is proposed in this paper, it uses the maximum likelihood function obtained by the improved A5CKF algorithm in the parallel filtering, updates the probability through the FL algorithm, and finally obtains the result through the output data fusion. Finally, by setting the same simulation model analysis, compared with IMMCKF [14], IMMA5CKF, and IMM5CKF [18], FLIMMA5CKF has better tracking effect and robustness, and the hysteresis is also improved. The rest of the sections are arranged as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, by setting the same tracking model simulation analysis, the algorithm has better convergence speed, tracking effect and robustness than the interactive multimodel cubature Kalman algorithm (IMMCKF), the interactive multimodel five-degree cubature Kalman algorithm (IMM5CKF) and the interactive multimodel adaptive five-degree cubature Kalman (IMMA5CKF).Symmetry 2019, 11, 767 2 of 16 third-order spherical-radial cubature rule was proposed by Haykin et al [13,14]; it is different from UKF, CKF has a strict mathematical formula to prove, it has been shown that CKF has better performance than UKF when the dimension of the system is greater than three [15]. In order to pursue better performance of CKF, 5CKF was proposed in the literature [16][17][18], and the simulation shows that 5CKF performance is better than CKF. For pursuing a better estimation performance of 5CKF filtering algorithm, combined with the improvement of Sage-Husa noise estimation in the literature [19], and the combination with the corresponding filtering algorithm in the literature [20][21][22][23], the adaptive five-degree cubature Kalman algorithm based on error covariance estimation is proposed, and it is used as a filtering algorithm under the IMM framework.In the IMM algorithm, the transition probability between models is performed by the Markov transition matrix.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The CKF [8] is proposed by Ienkaran Arasaratnam based on the Cubature rules with rigorous mathematical derivation. CKF is more accurate than the extended Kalman filter (EKF) [9] in a nonlinear filter and more accurate than the unscented Kalman filter (UKF) [10] in a high-degree nonlinear system filter [11]. Furthermore, the system of tracking an HGV is a high-degree nonlinear system.…”
Section: Introductionmentioning
confidence: 99%